Implementasi Sistem Pendukung Keputusan dalam Pemilihan Vendor IT Menerapkan Metode Weighted Product (WP) - Ahmad Rifqi; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
In the era of digital transformation, companies are required to strengthen their information technology (IT) infrastructure in order to compete effectively in an increasingly competitive market. Selection of the right IT vendor is crucial for the success of corporate projects that involve implementing, repairing, or upgrading IT systems. However, the vendor selection process is often complicated and complex, involving multiple criteria and considerations that must be carefully analyzed. To overcome these challenges, this study aims to implement a Decision Support System (SPK) based on the Weight Product (WP) method in selecting IT vendors for corporate projects. The WP method was chosen because of its ability to handle various criteria and provide the right weight for each criterion. The results of this study indicate that DSS based on the WP method can be an effective and efficient tool in helping companies choose the most suitable IT vendor for their projects. By reducing bias and subjective judgments, SPK can provide more objective and data-based results, which can increase the chances of project success and optimize company investment in information technology. This research contributes to companies facing the challenges of selecting IT vendors with a more structured and measurable. It is hoped that the use of DSS based on the WP method can help companies increase their competitiveness and achieve business goals through the application of appropriate and efficient information technology.